Pretty Girl-13 - Coley, Liz (New York, NY : Katherine Tegen Books, 2013)
Sixteen-year-old Angie finds herself in her neighborhood with no recollection of her abduction or the three years that have passed since, until alternate personalities start telling her their stories through letters and recordings.
Keywords: Amnesia -- Fiction; Multiple personality -- Fiction; Psychotherapy -- Fiction; Kidnapping -- Fiction; Family life -- California -- Fiction; Sexual abuse -- Fiction; Missing persons -- Fiction; California -- Fiction